2018
DOI: 10.3389/fphar.2018.01393
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate and Metformin Are Effective Add-On Treatments in Controlling Antipsychotic-Induced Weight Gain: A Systematic Review and Network Meta-Analysis

Abstract: Background: Antipsychotic drugs may lead to side effects such as obesity, diabetes, dyslipidemia, and cardiovascular disease. The current systematic review and network meta-analysis analyzes and provides an update on the clinical performance of these add-ons in comparison to placebo on body weight and body mass index (BMI) reductions.Methods: A comprehensive literature search was performed on electronic databases: PubMed (1946-), Embase (1974-), Cochrane library (1992-), and OpenGrey (2000-) until 31 July 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 67 publications
3
37
1
3
Order By: Relevance
“…Thus, blood lactate concentration, serum B 12 levels and folate levels should be regularly screened for patients with schizophrenia when they received metformin treatment 2 . Several meta-analyses 11,13,[29][30][31][32][33][34][35][36][37] had examined antipsychotic-induced body weight and metabolic abnormalities in schizophrenia, however, only a small number of them with comparatively smaller sample size meta-analyzed dyslipidemia as a secondary outcome 33,35,37 . This meta-analysis only included double-blind RCTs examining adjunctive metformin for dyslipidemia in schizophrenia, together with a large sample size increase the robustness and reliability of meta-analytic findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, blood lactate concentration, serum B 12 levels and folate levels should be regularly screened for patients with schizophrenia when they received metformin treatment 2 . Several meta-analyses 11,13,[29][30][31][32][33][34][35][36][37] had examined antipsychotic-induced body weight and metabolic abnormalities in schizophrenia, however, only a small number of them with comparatively smaller sample size meta-analyzed dyslipidemia as a secondary outcome 33,35,37 . This meta-analysis only included double-blind RCTs examining adjunctive metformin for dyslipidemia in schizophrenia, together with a large sample size increase the robustness and reliability of meta-analytic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Both international (PubMed, Cochrane Library, Psy-cINFO, and EMBASE) and Chinese (Chinese Journal Net, and WanFang) databases were independently searched to obtain relevant published RCTs by three investigators (WLJ, DBC, and FY) from their commencement dates to October 22, 2018, using the search terms as follows: ("metformin"[MeSH] OR metformin OR Dimethylbiguanidine OR Dimethylguanylguanidine OR Glucophage) AND ("dyslipidemias"[MeSH] OR Dyslipidemias OR Dyslipidemia OR Dyslipoproteinemias OR Dyslipoproteinemia OR metabolic OR lipid OR fats OR Hypolipidemic Agents OR cholesterol OR HDL OR LDL OR lipoprotein OR triglyceride OR adiponectin OR ghrelin OR leptin OR resistin OR chemerin OR omentin OR apelin or adipocytokine OR adipokine) AND ("schizophrenia"[Mesh] OR schizophrenic disorder OR disorder, schizophrenic OR schizophrenic disorders OR schizophrenia OR dementia praecox). The references of relevant reviews 11,13,[29][30][31][32][33][34][35][36][37] were also searched manually to avoid missing publications.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sibutramine, reboxetine, bupropion, orlistat, liraglutide, uoxetine, metformin, topiramate, and antagonism of the histamine 2 (H2) receptor, etc. were also reported to have signi cant effects on weight gain compared to placebo, [5][6][7][8] whereas, some previous studies' results were not consistent each other, even there are some con icting reports. 9 Metformin,a biguanide drug approved for treatment of type 2 diabetes, has been extensively studied for use of weight gain in the absence of diabetes in typically developing children.…”
Section: Introductionmentioning
confidence: 86%
“…[15][16][17] And it holds some promise as an adjunctive therapy for both overweight and treatment of psychotic symptoms. 5 Topiramate has the strongest mean weight loss compared with placebo, metformin, H2 receptor antagonists, and norepinephrine reuptake inhibitors in some reviews 5,8,18,19 although it has some adverse events which are possibly uncommon. Whereas, the effect of topiramate on patients with obesity caused by SGAs varied in different studies, some of the studies were either smaller samples or lack of placebo-controlled trial, or reported as other researches' additional results, and did not exactly infer the effects of topiramate on weight loss.…”
Section: Introductionmentioning
confidence: 99%